PELAKSANAAN PEMENUHAN HAK NARAPIDANA ANAK DI LEMBAGA PEMBINAAN KHUSUS ANAK KELAS IA TANGERANG - Nugroho Adipradana; Erwin Adipradipto; Tisa Windayani (Jurnal Perkotaan, 2019)
Abstract In criminal justice system, it is important to make sure that the rights of the inmates are both protected and properly fulfilled. This is even more essential in the case of inmate children, bearing in mind all the aspects attached on them. The rights are regulated in the Art.4 of Law No. 11/2012 on Criminal Justice System for Children’s Court and and also Art 22 Law No 12/1995 on Correctional Institution. This research observes and analyzes how is the implementation of those rights in Special Correctional Facilities for Children Class 1A Tangerang. The method used is yuridis-empiris which dominated by observation and interviews. The result of the study is that the Special Correctional Facility observed has carried out the rights for inmate children in a suffice manner which comprises right for education, access to health, legal aid, access to information and others.